Estudo do sistema de drenagem urbana no Jardim Interlagos em Apucarana-PR - Barros, Luan Gabriel Beluco da Silva de (2023)
The management and handling of rainwater and a well structured drainage system are of paramount importance to a city. A proper dimensioning of the urban drainage system ansure an effective removal of rainwater from urban areas and improve quality of life for the population. This study aims to analyze the existing drainage system in Jardim Interlagos, a neighborhood located in Apucarana, Paraná. The main objective is to compare the existing system with na ideal designed system in order to identify underdimensioned segments of the system. To achive this, all necessary parameters for dimensioning were obteined, and used the project provided by the municipal Department of Public Works, designed in september 2000. Sections os the drainage system were identified that could not handle the flow it was subjected to and sections with excessively high velocities. Therefore, it was necesary to resize these sections by modifyng the diameter or inclination to attend the local demands.